Graduate student profile: Aini Norhidayah Mohamed, Msc (industrial chemistry) candidate - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Aini Norhidayah Mohamed was born in Triang (Pahang) on October 6 1985, the last child of six siblings. Aini completed secondary education at Sekolah Menengah Sains Sultan Haji Ahmad Shah (Pekan) and pre-university at Kolej Matrikulasi Pulau Pinang before going off to Universiti Kebangsaan Malaysia to study Plant Biotechnology.